TOMATO (Solanum lycopersicum L.) RESPONSE TO BAMBOO SHOOT LIQUID ORGANIC FERTILIZER APPLICATION - Tanari, Yulinda; Jayanti, Kamelia Dwi (Universitas Trilogi, 2024)
ABSTRACTOne simple indicator of balanced nutrition is the consumption of vegetables of 250 grams per day. Therefore, the increasing population demands an adequate supply of vegetables. Tomato is a vegetable that contains nutrients and has health benefits. Additionally, tomato is also one of the vegetables that generate foreign exchange for the country through exports. One possible way to increase tomato production is the use of Liquid Organic Fertilizer (LOF) made from Bamboo Shoots. Bamboo shoots LOF contains essential nutrients for the growth and development of tomato plants. The method used in this study was a Randomized Complete Block Design (RCBD) with 5 treatments and 4 replications, namely P0: Without LOF, P1: 50 ml bamboo shoots LOF per liter, P2: 100 mL bamboo shoots LOF per liter, P3: 150 mL bamboo shoots LOF per liter, and P4: 200 mL bamboo shoots LOF per liter. The results showed that the application of LOF had a significant effect on increasing the number and weight of tomato fruits, with the best concentration at 100 mL LOF per liter of water.